Diversity of Fabaceae in the Universitas Palangka Raya Area, Central Kalimantan, Indonesia - Ria Windi Lestari; Yuli Wulan Sari; Umi Novita Fitriah; Fadhila Aziz; Decenly Decenly (Journal of Biotropical Research and Nature Technology, 2026)
The Fabaceae family (Leguminosae), belonging to the order Fabales, comprises approximately 630 genera and 18,000 species distributed worldwide. According to the modern phylogenetic classification proposed by the Legume Phylogeny Working Group (LPWG), Fabaceae is divided into six subfamilies: Cercidoideae, Detarioideae, Duparquetioideae, Dialioideae, Caesalpinioideae, and Faboideae. Members of this family include herbs, shrubs, and trees, with a wide range of ecological adaptations in tropical ecosystems. This study was conducted within the campus area of Universitas Palangka Raya to document the diversity of Fabaceae species, which has not been comprehensively recorded in this region. A field survey method was applied to collect and identify specimens based on morphological characteristics. A total of 18 Fabaceae species were recorded. Caesalpinioideae comprised 11 species, Faboideae 6 species, and Detarioideae 1 species. Growth forms included herbs, shrubs, and trees. Based on ecological status, 6 species were classified as native and 12 as introduced according to Plants of the World Online (POWO). This study provides baseline floristic data on Fabaceae diversity in the Universitas Palangka Raya area and contributes to taxonomic and biodiversity documentation in Central Kalimantan.